1990
DOI: 10.1111/j.1432-1033.1990.tb15401.x
|View full text |Cite
|
Sign up to set email alerts
|

The contacts of yeast tRNASer with seryl‐tRNA synthetase studied by footprinting experiments

Abstract: Yeast tRNA(Ser) is a member of the class II tRNAs, whose characteristic is the presence of an extended variable loop. This additional structural feature raises questions about the recognition of these class II tRNAs by their cognate synthetase and the possibility of the involvement of the extra arm in the recognition process. A footprinting study of yeast tRNA(Ser) complexed with its cognate synthetase, yeast seryl-tRNA synthetase (an alpha 2 dimer), was undertaken. Chemical (ethylnitrosourea) and enzymatic (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 57 publications
(19 reference statements)
0
37
0
Order By: Relevance
“…The lysate was clarified by centrifugation at 100,000 ϫ g for 90 min at 4°C, giving about 10 ml extract with 10 mg of protein/ml. SerRS was purified by chromatography on DEAE-cellulose (DE52, Whatman) and phosphocellulose (P-11 Whatman) columns, as described previously (20,21). Protein extract was dialyzed against 20 mM potassium phosphate buffer, pH 7.2, containing 10% glycerol, 3 mM DTT, 0.1 mM EDTA, and 0.2 mM PMSF and applied onto a DEAEcellulose column (1.5 ϫ 14 cm) equilibrated in the same buffer.…”
Section: General Procedures-[mentioning
confidence: 99%
See 1 more Smart Citation
“…The lysate was clarified by centrifugation at 100,000 ϫ g for 90 min at 4°C, giving about 10 ml extract with 10 mg of protein/ml. SerRS was purified by chromatography on DEAE-cellulose (DE52, Whatman) and phosphocellulose (P-11 Whatman) columns, as described previously (20,21). Protein extract was dialyzed against 20 mM potassium phosphate buffer, pH 7.2, containing 10% glycerol, 3 mM DTT, 0.1 mM EDTA, and 0.2 mM PMSF and applied onto a DEAEcellulose column (1.5 ϫ 14 cm) equilibrated in the same buffer.…”
Section: General Procedures-[mentioning
confidence: 99%
“…Full-length SerRS was purified to apparent homogeneity (Fig. 3A, lanes e and f) by a quick two-step chromatographic procedure that involves fractionation on DEAE-cellulose and phosphocellulose columns (20,21) as the important steps in isolation of SerRS from non-overproducing yeast strains. The procedure allows the purification of 1 mg of protein from 1 g of yeast cells, with a specific activity of 115 nmol mg Ϫ1 min…”
Section: Overexpression and Purification Of Wild-type And Truncatedmentioning
confidence: 99%
“…The long variable arm has been implicated in the recognition of E. coli tRNA Tyr (Himeno et al 1990) and is an idiosyncratic feature that could interact with the idiosyncratic amino-terminal domain of the CYT-18 protein and contribute to the Neurospora mt tRNA Tyr being a better inhibitor of splicing than is E. coli tRNA Tyr. In the case of yeast tRNA set, which also has a long variable arm, footprinting experiments have shown that SerRS binds to both the variable arm and the base of the anticodon stem (Dock-Bregeon et al 1990). If the situation is similar for the Neurospora mt TyrRS, a key structure involved in recognition may be the cognate of the variable arm, P7, hinged off the cognate of the anticodon arm, P4/P6 (cf.…”
Section: P8mentioning
confidence: 99%
“…Ser have revealed that it contains the major identity element of tRNA Ser (11)(12)(13)(14). The recognition mechanism of SerRS thus appears to be evolutionarily conserved in both prokaryote and eukaryotic cytoplasm.…”
mentioning
confidence: 99%